Histological evaluation of hydroxyapatite granules with and without platelet-rich plasma versus an autologous bone graft : comparative study of biomaterials used for spinal fusion in a New Zealand white rabbit model - Zakaria@Mohamad, Zamzuri; Che Seman, Che Nor Zarida; Buyong, Zunariah; Sharifudin, Mohd Ariff; Zulkifly, Ahmad Hafiz; Khalid, Kamarul Ariffin (2016)
Objectives: Hydroxyapatite (HA) has osteoconductive properties and is widely used as a bone graft substitute. Platelet-rich plasma (PRP) is an autologous product with osteoinductive effects. Hypothetically, a combination of both would augment the bone formation effect of HA and widen its application in spinal fusion surgeries. This study aimed to compare new bone formation with HA granules alone and in combination with PRP versus an autologous bone graft during a lumbar intertransverse process spinal fusion. Methods: A total of 16 adult New Zealand white rabbits underwent single-level bilateral intertransverse process fusion at the L5–L6 vertebrae. One side of the spine received either HA granules alone or a combination of HA granules and PRP, while the contralateral side received an autologous bone graft. Four animals each from the HA group and the HA plus PRP group versus the autograft group were assessed either at six or 16 weeks by undecalcified histology and histomorphometry. The mean percentage of new bone areas over the corresponding fusion masses were compared between groups. Results: No signi cant di erence in new bone formation was observed between the HA and HA plus PRP groups at six or 16 weeks. The autograft group had significantly more new bone formation at six and 16 weeks (P = 0.004 and <0.001, respectively). Conclusion: An autologous bone graft remains superior to HA granules, with or without PRP. HA granules demonstrated an excellent osteoconductive scaffold but had poor biodegradability. While PRP enhances the properties of HA granules, these biomaterials do not have a synergistic effect.